Enzymatic synthesis of low-trans blends from fractionated mustard oil and palm stearin with linoleic acid by response surface methodology (Journal of the Bangladesh Agricultural University, 2010)
Low-trans blend (LTB) was produced from the fractionated mustard oil (solid phase, S-MO) and palm stearin (PS) through lipase-catalyzed reaction, in which linoleic acid (LA) was intentionally incorporated. For optimizing the reaction condition, response surface methodology (RSM) was employed with three reaction variables such as substrate mole ratio of S-MO to PS (X1), reaction temperature (X2) and reaction time (X3). The predictive models were adequate and reproducible due to no significant lack of fit and the P-value of the model was very small ω6/ω3 ratio, and satisfactory level of coefficient of determination (R2 = 0.89) for ω6/ω3 ratio. The ω6/ω3 ratio of LTB was affected by substrate mole ratio and reaction temperature but reaction time had no significant effect. For considering the ω6/ω3 ratio, the optimum condition found 1:1.7 substrate mole ratio, 61.42 _ reaction temperature and 25.85 h reaction time. Keywords: Low-trans blend; Mustard oil; Palm stearin; Lipase-catalyzed reaction; Response surface methodology; Solid fat content DOI: 10.3329/jbau.v7i1.4974 J. Bangladesh Agril. Univ. 7(1): 125-132, 2009